Antibody Responses Elicited against the Treponema pallidum Repeat Proteins Differ during Infection with Different Isolates of Treponema pallidum subsp. pallidum - Leader, Brandon T. (American Society for Microbiology, 2003)
Variation in the expression of the different Tpr proteins in the syphilis spirochete, Treponema pallidum subsp. pallidum, may have important implications in its ability to evade host immune detection and cause persistent infection. In the present study we examined the pattern of antibody responsiveness to different Tpr members during infection with three isolates of T. pallidum. There was variability in the specificities and temporal patterns of reactivity of the antibodies elicited against the individual Tpr proteins, suggesting that isolates may express different repertoires of Tpr proteins during infection.